Pengaruh Pengendalian Internal, Sistim Informasi Akuntansi Terhadap Efisiensi Biaya, Efektivitas Pelayanan Medis dan Non Medis Pada PT Rumah Sakit Pelni - Rivan Wibowo (Jurnal Buana Akuntansi, 2019)
The purpose of this study was to determine the effect of the Internal Control and Accounting Information Systems Cost Efficiency And Effectiveness Of Medical And Non-Medical Services (Studies in Hospital Pelni). The independent variable of this study is the Internal Control and Accounting Information Systems. The dependent variable of this study is Cost-Efficiency and Effectiveness of Medical and Non-Medical Services. The research method used is explanatory survey with a cross-sectional methods, while the sampling technique is convenience sampling with instruments of research using questionnaires in 58 respondents in Pelni Hospital. Data were analyzed quantitatively by regression analysis. Results of the study (1) Internal Control Influential Efficiency Gains and Cost Effectiveness of Medical and Non-Medical Services (2) Impact of Accounting Information Systems Gains Efficiency And Cost Effectiveness of Medical and Non-Medical Services (3) Simultaneously Internal Control and Accounting Information Systems Influential Significant Cost Efficiency And Effectiveness of Medical and Non-Medical Services. Keywords: Internal Control, Accounting Information Systems, Efficiency and Cost Effectiveness of Medical and Non-Medical Services